DURABILITY OF PROTECTIVE DECORATIVE COATINGS FORMED ON THERMALLY MODIFIED WOOD PANELS - Georgiev, Zhivko (Innovation in Woodworking Industry and Engineering design, 2012)
The durability of polymer coatings, formed on thermally modified spruce wood articles outdoor exposed was investigated. It was applied two regular coating systems (alkyd system; waterborne acrylate system). It was made some marks on destructions in wood and coating during four year outdoor exploitation. It is discover that after four years exploitation waterborne acrylate protection have a local destruction in crater form in the beginning and totally removed in these zone after, while alkyd system is practically destructed in zone near to end. Thermally modified wood without coating become grayish and cracked in the ends. This tendency is also valid for alkyd protection, but not really valid for waterborne acrylate. The coatings do it with alkyd system protection has character destruction in zone of summer timber, which is more underlined for tangential samples.